2015
DOI: 10.7314/apjcp.2015.16.16.7077
|View full text |Cite
|
Sign up to set email alerts
|

Do Human Papilloma Viruses Play Any Role in Oral Squamous Cell Carcinoma in North Indians?

Abstract: Background: Oral squamous cell carcinoma (OSCC) is the most prevalent malignancy among males in India. While tobacco and alcohol are main aetiological factors, human papilloma virus (HPV) presence has surprisingly increased in head and neck Squamous Cell Carcinoma (HNSCC) in the past two decade but its frequency in OSCCS is still uncertain. We aim to explore the frequency of HPV and its major genotypes in North Indian patients and their association with clinicopathological and histopathological features and p1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 35 publications
3
21
0
Order By: Relevance
“…In our previous study, we have explored the frequency of HPV and its major genotypes in North Indian population with OSCC and their association with clinicopathological and histopathological features and p16 expression pattern. We found contradictory association between HPV and p16 . Since the mucosal surface of oral cavity is exposed to both HPV and chemical carcinogens (tobacco and alcohol) simultaneously, the carcinogenesis of oral cancer might be different and need to be explored.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In our previous study, we have explored the frequency of HPV and its major genotypes in North Indian population with OSCC and their association with clinicopathological and histopathological features and p16 expression pattern. We found contradictory association between HPV and p16 . Since the mucosal surface of oral cavity is exposed to both HPV and chemical carcinogens (tobacco and alcohol) simultaneously, the carcinogenesis of oral cancer might be different and need to be explored.…”
Section: Introductionmentioning
confidence: 81%
“…Further, identification of high‐risk HPV16 and 18 was done by type‐specific conventional PCR . Methodology in detail was described in our previous study . The diagnostic criteria implemented, defined those cases as HPV positive which were positive by any of two methods.…”
Section: Methodsmentioning
confidence: 99%
“…Singh et al . [8] reported the prevalence of HPV infection in patients with OSCC involved in the consumption of tobacco and betel leaves. They also revealed that the concordance of HPV-induced OSCC is significantly more in men than in women ( P = 0.02).…”
Section: Discussionmentioning
confidence: 99%
“…Use of p16 protein as a surrogate marker to assess the potential etiological role of HPV in OSCC in our population is not reliable. 58 In our attempt to elicit the differences in the expression pattern of p16 and p53 in HPV-positive and HPV-negative OSCC, if any we observed that risk factors including oral tobacco consumption and alcohol were present in all these ten p16-positive cases. Presence of mutant-type p53 and exposure to tobacco-related risk factors in both HPV-positive and negative cases suggest existence of p53-related carcinogenesis in HPVpositive cases in Indian population.…”
Section: Controversies In the Role Of Hpv In Osccmentioning
confidence: 99%